Social Work in Addictions and Health Care - NEAMȚU, Nicoleta; ȘTEFANI, Sebastian Claudiu (Presa Universitară Clujeană, 2023)
This volume includes a selection of papers presented at the thirteenth edition of the international conference: "Social Work in the Addictions and Health Care – Interdisciplinary Collaboration to Improve Quality of Services and Quality of Life", which took place in Alba Iulia during December 9-10. The conference organized by the ”1 Decembrie 1918” University of Alba Iulia aimed to bring together researchers and practitioners in the field of social work applied in the field of health and addictions to share the results of research and professional practice.